A monograph of Aspergillus section Candidi - Glässnerová, K; Sklenář, F; Jurjević, Ž; Houbraken, J; Yaguchi, T; Visagie, C M; Gené, J; Siqueira, J P Z; Kubátová, A; Kolařík, M; Hubka, V (Studies in mycology, 2022)
Aspergillus section Candidi encompasses white- or yellow-sporulating species mostly isolated from indoor and cave environments, food, feed, clinical material, soil and dung. Their identification is non-trivial due to largely uniform morphology. This study aims to re-evaluate the species boundaries in the section Candidi and present an overview of all existing species along with information on their ecology. For the analyses, we assembled a set of 113 strains with diverse origin. For the molecular analyses, we used DNA sequences of three house-keeping genes (benA, CaM and RPB2) and employed species delimitation methods based on a multispecies coalescent model. Classical phylogenetic methods and genealogical concordance phylogenetic species recognition (GCPSR) approaches were used for comparison. Phenotypic studies involved comparisons of macromorphology on four cultivation media, seven micromorphological characters and growth at temperatures ranging from 10 to 45 °C. Based on the integrative approach comprising four criteria (phylogenetic and phenotypic), all currently accepted species gained support, while two new species are proposed (A. magnus and A. tenebricus). In addition, we proposed the new name A. neotritici to replace an invalidly described A. tritici. The revised section Candidi now encompasses nine species, some of which manifest a high level of intraspecific genetic and/or phenotypic variability (e.g., A. subalbidus and A. campestris) while others are more uniform (e.g., A. candidus or A. pragensis). The growth rates on different media and at different temperatures, colony colours, production of soluble pigments, stipe dimensions and vesicle diameters contributed the most to the phenotypic species differentiation. Taxonomic novelties: New species: Aspergillus magnus Glässnerová & Hubka; Aspergillus neotritici Glässnerová & Hubka; Aspergillus tenebricus Houbraken, Glässnerová & Hubka. Citation: Glässnerová K, Sklenář F, Jurjević Ž, Houbraken J, Yaguchi T, Visagie CM, Gené J, Siqueira JPZ, Kubátová A, Kolařík M, Hubka V (2022). A monograph of Aspergillus section Candidi. Studies in Mycology 102: 1-51. doi: 10.3114/sim.2022.102.01.
Keywords: Aspergillus candidus; integrative taxonomy; intraspecific variability; multispecies coalescent model; genealogical concordance; Aspergillus tritici